Aflatoxins stunt growth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Research by the International Institute of Tropical Agriculture (IITA) and the University of Leeds, UK, has revealed that aflatoxins in food are hampering children s growth in Benin and Togo. Elevated levels of aflatoxins in the blood of 475 out of...